1994
DOI: 10.1086/209371
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Language Effects in Ethnic Advertising: A Sociolinguistic Perspective

Abstract: The authors apply sociolinguistic theories of accommodation to investigate how consumers in a minority subculture respond to the use of their ethnic language in advertising. Specifically, Hispanic consUrT1ers' responses to the varying degrees of Spanish-language usage in print advertising were examined. It was found that the effects of Spanish usage in advertising can be usefully explained by accommodation theory. Spanish-language advertising increased Hispanic consumers' perception of advertiser sensitivity t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
129
1
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(134 citation statements)
references
References 20 publications
(23 reference statements)
3
129
1
1
Order By: Relevance
“…In fact, a new TV network, SíTV, is targeting young Hispanics in English (Grow, 2006). Also, one must consider whether assimilated Hispanics resent bilingual packaging (Koslow, Shamdasani, & Touchstone, 1994).…”
Section: General Discussion and Further Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, a new TV network, SíTV, is targeting young Hispanics in English (Grow, 2006). Also, one must consider whether assimilated Hispanics resent bilingual packaging (Koslow, Shamdasani, & Touchstone, 1994).…”
Section: General Discussion and Further Researchmentioning
confidence: 99%
“…That is, marketers are bringing this controversy to all on a daily basis through advertising and other marketing activities. This desire to reach Hispanics is not surprising, because the Hispanic market represents over $600 billion in buying power (Zimmerman, 2005), and academic research using accommodation theory has shown that people prefer marketing messages in their own, native language (Koslow, Shamdasani, & Touchstone, 1994). As such, instructions and packages of products sold in the United States are often printed in both English and Spanish despite the fact that only a small percentage of purchasers need the information to be presented in Spanish to make an informed choice.…”
Section: Introductionmentioning
confidence: 99%
“…The survey instrument was developed using existing measurements from the advertising and marketing communication literatures on measures such as company credibility (Coulson, 1980;Newell & Goldsmith, 2001), company image (Annan, 1999;Fombrun, 1996;Gray, Armstrong & Farley, 2003), perceived sensitivity (Koslow, Shamdasani & Touchstone, 1994), attitude toward the company (Gregory, Munch & Peterson, 2002;Simard, Taylor & Giles, 1976), attitude toward advertisements (Ford, LaTour & Henthorne, 1995) and advertising targets (Koslow, Shamdasani & Touchstone, 1994). For all measures, a 7-point Likert type scale was used, with anchors ranging from strongly agree (1) to strongly disagree (7).…”
Section: Methodsmentioning
confidence: 99%
“…Sunnafrank and Miller (1981) observe that people feel attracted to others with whom they can communicate well. In a language context, attraction results from lowered language differences, such that the speaker becomes more similar to the listener (Koslow, Shamdasani, and Touchstone, 1994;Montoya and Briggs 2013). Therefore, the language that service providers use might serve as a source of similarity, and when consumers and service providers are more similar, consumers are more likely to spread positive word of mouth.…”
Section: Speech Accommodation Theory As a Theoretical Anchormentioning
confidence: 99%